(untitled) (Nepal Journal of Environmental Science, 2015)
The purpose of this study was to develop a simple and sensitive high performance liquid chromatography (HPLC) method for determination of glyphosate (GP) residues in soybean grains. From soybean matrix, glyphosate was extracted with a mixture of water and methanol (4:1, v/v) from soybean samples followed by protein precipitation with equal volume of methanol. No preconcentration and further clean up of the sample were required. Pre-column derivatization was carried out with excess amount of 9- fluorenylmethyl chloroformate (FMOC-Cl) in the presence of borate buffer. The gradient program developed in this method was successfully applied to a reverse phase HPLC system with a C18 column (ACE 5 μm 4.6 x 250 mm), and eluted with a mobile phase consisting of 50 mM phosphate buffer, pH 2.5, and acetonitrile at the flow rate of 0.8 ml/min and fluorescence detection. Parameters and conditions affecting extraction, derivatization reaction and chromatographic separation were systematically examined. Linearity of the method ranged from 0.005 - 1.0 μg/ml. The correlation coefficient (r2) of calibration curve for glyphosate in soybean sample was found to be 0.99929. The limit of detection (LOD) and limit of quantitation (LOQ) values were determined to be 0.125 mg/kg and 0.25 mg/kg, respectively. Average recovery was 95.2%. Repeatability and intermediate precision calculated on the basis of peak area were excellent and showed relative standard deviation ranged from 0.15 - 1.29% and 1.15 - 3.87%, respectively. The developed method has been successfully applied for determination of glyphosate residues in soybean grains obtained from Thailand and Nepal. Soybean samples (53) from two different lots were analyzed and glyphosate residues ranged from 0.23 mg/kg to 5.06 mg/kg. Almost 50% soybean samples contained nearly consistent residue levels in both lots but in remaining samples there was a significant variation of glyphosate levels between two lots. Relatively higher residues were detected in samples from Thailand (0.27-5.06 mg/kg) compared to Nepal (0.23-0.99 mg/kg). The results suggest that the proposed method can be used to determine glyphosate residues in foods derived from soybean and other crops such as corn, cotton, wheat, etc. where glyphosate is widely applied to these crops.